Why snakebite patients in Myanmar seek traditional healers despite availability of biomedical care at hospitals? Community perspectives on reasons - Schioldann, E; Mahmood, M; Kyaw, M; Halliday, D; Thwin, K; Chit, N; Cumming, R; Bacon, D; Alfred, S; White, J; Warrell, D; Peh, C (Public Library of Science, 2018)
Background Snakebite is a major public health problem in many developing countries. Farmers are particularly exposed to snakes, and due to their rural location often experience delays in accessing formal healthcare. The reasons to use traditional healers may include difficulties in accessing formal healthcare, certain beliefs about snakes and snake venom, tradition, and trust in the capacity of traditional healers. Traditional healing, however, may have serious consequences in terms of delays or added complications. There is little in-depth current information about the reasons for its continued use for snakebite. As part of a health services development project to improve health outcomes for snakebite patients, community attitudes to the use of traditional healers were explored in the Mandalay region of Myanmar. Methodology & findings With the objective of learning from local communities, information was generated in three communities using participatory appraisal methods with the communities, and focus group discussions with the local healthcare staff. Many snakebite victims in these communities use traditional healing. Reasons include transport difficulties, low cost for traditional healing, inadequacy of anti-snake venom in the formal healthcare sector, and traditional beliefs, as traditional healing practices are rooted in many cultural and traditional factors. The communities reported that even if access to medical care were improved, traditional healing would continue to be used. Conclusion These findings point to the need for working with traditional healers for prevention, appropriate first aid and timely access to effective treatment for snakebite.